The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s10286-018-0508-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of renal sympathetic innervation: recent insights beyond blood pressure control

Abstract: Renal afferent and efferent sympathetic nerves are involved in the regulation of blood pressure and have a pathophysiological role in hypertension. Additionally, several conditions that frequently coexist with hypertension, such as heart failure, obstructive sleep apnea, atrial fibrillation, renal dysfunction, and metabolic syndrome, demonstrate enhanced sympathetic activity. Renal denervation (RDN) is an approach to reduce renal and whole body sympathetic activation. Experimental models indicate that RDN has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 83 publications
(102 reference statements)
1
18
0
1
Order By: Relevance
“…Solid evidence has accumulated indicating that a deranged renal sympathetic activity could be detrimental in a series of other pathological conditions including renal disease, arrhythmias, obstructive sleep apnea, and metabolic syndrome (Linz et al, 2018). Future therapeutic targets of renal nerve ablation could move beyond the treatment of resistant hypertension.…”
Section: Future Scenarios Of Clinical Application Of Renal Nerve Ablamentioning
confidence: 99%
“…Solid evidence has accumulated indicating that a deranged renal sympathetic activity could be detrimental in a series of other pathological conditions including renal disease, arrhythmias, obstructive sleep apnea, and metabolic syndrome (Linz et al, 2018). Future therapeutic targets of renal nerve ablation could move beyond the treatment of resistant hypertension.…”
Section: Future Scenarios Of Clinical Application Of Renal Nerve Ablamentioning
confidence: 99%
“…A recent meta‐analysis of relatively small feasibility studies suggests that renal denervation may improve left ventricular function in patients with dilated heart disease . In addition, the potential of renal denervation in reducing atrial fibrillation and ventricular arrhythmias has been shown in a variety of animal models . Thus far, however, the impact of renal denervation has not been evaluated in Chagas cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, the potential of renal denervation in reducing atrial fibrillation and ventricular arrhythmias has been shown in a variety of animal models. 21 Thus far, however, the impact of renal denervation has not been evaluated in Chagas cardiomyopathy.…”
mentioning
confidence: 99%
“…In their state-of-the-art review, Linz and colleagues discuss the relevance of renal afferent and efferent sympathetic nerves in blood regulation and hypertension, with focus on the potential of and lessons learned from renal denervation [6]. They further analyze the comorbidities of hypertension that also share sympathetic hyperactivity, such as heart failure, sleep apnea, and atrial fibrillation, and how renal modulation can not only be beneficial for the treatment of hypertension, but also for the management of life-threatening arrhythmias.…”
mentioning
confidence: 99%